Penciptaan Naskah Drama Pemberontakan Sisifus - RANO SUMARNO (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2009)
The Rebellion of Syssiphus. The Rebellion of Syssiphus play script is an effort to response suicide phenomenonin Indonesia. Joining two different social lives among human life in Indonesia and Greek mythology constructsthis creation as a surrealism play script. The purpose of this creation is: 1) to create a joint script of two differentrealms between Sissyphus’ life and recent reality of Indonesian people’s life in surrealist plot, (2) to produce a scriptconstantly contextual with man’s problem in life, (3) to enrich Indonesia Drama documentation through a scriptwith high motivational contents as an alternative of destiny. As a anti-suicide campaign for Indonesians, the authorinvokes a brilliant thinking of existentialist philosopher, Albert Camus, within the script to be performed andwatched. The implementation is not wholesome, but adapting Pancasila values. Therefore, this script is importantas a reference for students who teach and perform absurd scripts. Most drama observers say that the emergence ofabsurd script proposed by group of dramatist in 1950’s could not be released from Camus’ thought